Statics and Influence Functions - from a Modern Perspective - Hartmann, Friedel; Jahn, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The book teaches engineers many new things about a classical topic which suddenly is again in the center of interest because of its relevance for finite element analysis, for the accuracy of computational methods. It shows that influence functions play a fundamental role in the finite element analysis of structures and practically all of linear computational mechanics. It also strives to add new and important insights into modern structural analysis and into computational mechanics by establishing the central role of influence functions for the numerical analysis and to lay a new foundation to the energy and variational principles.
Basics -- Betti's theorem -- Finite elements -- Betti extended -- Stiffness changes and reanalysis -- Singularities -- Energy principles of plates and slabs and supplements -- References.
Keywords: Mechanics, Applied; Solids; Solid Mechanics